Perioperative Hemodynamic Optimization Using Goal-Directed Therapy in High-Risk Cardiac Patients Undergoing Major Abdominal Surgery: A Prospective Clinical Study - Nawaz Ali Dal, Nouman Akram, Junaid Ahmad, Rahil Mahmoodur Rahman, Abrar Ul Hassan Pirzada, Alvina Khan, Afshan Nafees, Laiba Naseem Khuhawer (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Patients with high risk for cardiac complications who are undergoing major abdominal surgery are very likely to experience perioperative hemodynamic instability, hypoperfusion, cardiovascular complications, and organ dysfunction after surgery. Goal directed therapy (GDT) is a new personal approach to hemodynamic optimization that is directed toward the goal of improving tissue perfusion and decreasing post operative morbidity. Objective: To assess the outcome of improving hemodynamic stability and postoperative outcome by implementing a strategy of goal-directed therapy perioperatively in high-risk cardiac patients with major abdominal surgery. Materials and Methods: The study was conducted at Liaquat University of Medical and Health Sciences, Department of General Surgery and at Dr. Ziauddin Hospital from January 2023 to July 2023. There were 120 high-risk cardiac patients who were undergoing elective major abdominal surgery included. The patients were split into two groups: Goal-Directed Therapy group (n=60) and Conventional Hemodynamic Management group (n=60). Hemodynamic parameters measured were mean arterial pressure, cardiac index, serum lactate, urine output, vasopressor requirement and postoperative clinical outcomes. Data was analyzed statistically with SPSS version 26.0 and statistically significant p<0.05 was used. Results: Goal-directed therapy group had significantly better intraoperative hemodynamic status than the conventional group. The mean arterial pressure and cardiac index were significantly elevated in the GDT group, while the serum lactate and the amount of vasopressors used were significantly reduced. The rate of postoperative cardiovascular complications was 13.3% among GDT patients while it was 35.0% among conventional patients. There was a significant difference between the GDT group and the control group (11.7% vs 30.0%) for acute kidney injury. Patients who received goal-directed therapy also had a significantly shorter ICU stay and hospital stay. Conclusion: Perioperative goal-directed therapy significantly improves hemodynamic optimization and postoperative recovery in high-risk cardiac patients undergoing major abdominal surgery. Keywords: Goal-directed therapy; Hemodynamic optimization; Major abdominal surgery; High-risk cardiac patients; Perioperative care; Cardiac index; Postoperative complications